SOSIALSASI DAN EDUKASI AWERNESS TERHADAP PENGGUNA SKINCARE DI ALANGAN GENERASI Z AWARENESS SOCIALIZATION AND EDUCATION TOWARDS SKINCARE USERS AMONG GENERATION Z - Malik, Fadhliyah; Handoyo, Muhammad; Mulviana, Astrawanda; Zakhrafia, Ainun; Fea, Waode Aisyah; Saputri, Nita; Yani, Rica Dwi (MAJU : Indonesian Journal of Community Empowerment, 2025)
Mercury and hydroquinone are ingredients that are often misused by illegal cosmetic manufacturers as skin whitening ingredients by inhibiting melanin synthesis, but the side effects are very dangerous to health such as damage to the central nervous system and cancer. This activity was carried out with the aim of providing knowledge and skills to students of SMA Negeri 6 Kendari to be aware of skincare users among Gen Z skincare and how to recognize their physical characteristics. This activity was carried out using the counseling and question and answer method on the material on the dangers of using whitening cosmetics containing mercury and hydroquinone followed by training in checking the physical characteristics of skincare and how to ensure skincare registration numbers using a cellphone. Furthermore, students were given a questionnaire with the aim of determining students' understanding after being given counseling. The results of the questionnaire showed that 98% of students understood how to choose safe cosmetics and could visually identify cosmetics in cosmetics containing mercury and hydroquinone.